Omission of Axillary Staging and Survival in Elderly Women With Early Stage Breast Cancer: A Population-Based Cohort Study. Issue 2 (25th June 2022) - Castelo, Matthew; Hansen, Bettina E.; Paszat, Lawrence; Baxter, Nancy N.; Scheer, Adena S.
Abstract : Objectives: Determine if axillary staging is associated with survival in elderly women with breast cancer. Background: Axillary staging in women ≥ 70 years with early-stage breast cancer is controversial. Older randomized evidence has not shown axillary staging improves survival, but recent observational studies have been mixed and widespread de-implementation of the practice has not occurred. Methods: This was a population-based cohort study using the Surveillance, Epidemiology, and End Results registry. Women ≥ 70 years diagnosed with T1–T2 invasive breast cancer from 2005 to 2015 were included. Overlap propensity score weighting was used to adjust for confounders. Overall survival (OS) was determined and hazard ratios (HRs) reported with 95% confidence intervals (CIs). Breast cancer-specific survival (BCSS) was determined using competing risks analysis and subdistribution hazard ratios (sdHRs) reported. Additional adjustment was performed for receipt of chemotherapy and radiotherapy. Results: One hundred forty-four thousand three hundred twenty-nine elderly women were included, of whom 22, 621 (15.7%) did not undergo axillary staging. After overlap propensity score weighting, baseline characteristics were well balanced between the 2 groups. Women who did not undergo axillary staging were significantly less likely to receive chemotherapy (adjusted relative risk, 0.58; 95% CI, 0.54–0.62) or radiotherapy (adjusted relative risk, 0.53; 95% CI, 0.52–0.54), and had significantly worse OS (adjusted HR, 1.22; 95% CI, 1.19–1.25), and BCSS (adjusted sdHR, 1.14; 95% CI, 1.08–1.21) compared to those that had staging. Conclusions: These findings suggest elderly women with early-stage breast cancer who do not undergo axillary staging experience worse outcomes. Reasons for this disparity may be multifactorial and require further investigation.